Interactive Material for the Acquisition of the Alphabetic Code in Second Grade Primary School - Andrade Dávila, Diana Raquel; Rivera Roldán, Mayra; Arias Duque, Sisa; Espinoza López, Asucena; Ruiz Erazo, Rosa Lida (Revista Ecos de la Academia, 2025)
The COVID-19 pandemic profoundly transformed educational processes, positioning Information and Communication Technologies (ICTs) as essential tools for ensuring the continuity of learning in emergency contexts. However, this transition revealed significant weaknesses in the development of literacy skills, particularly among second-grade students in primary school—a critical stage for the acquisition of the alphabetic code. In response to this situation, the present study aimed to analyze the interactive resources used for the literacy development, with a specific focus on the acquisition of the alphabetic code, among students at the “Otavalo Valle del Amanecer” Primary School during the 2023–2024 academic year. Methodologically, a quantitative approach with a descriptive design was employed, using surveys administered to teachers and legal guardians to identify needs and perceptions regarding the initial literacy process. The results revealed a high demand for supplementary resources to strengthen the teaching of the alphabetic code. The study concludes that the use of interactive digital materials constitutes an effective and necessary pedagogical strategy in this educational context to support literacy development in hybrid or virtual learning environments.